PENGENAAN PAJAK ATAS PENGALIHAN HAK ATAS TANAH DAN BANGUNAN MELALUI PPJB (PERJANJIAN PENGIKATAN JUAL BELI) LUNAS YANG DISERTAI KUASA JUAL - RAYMOND SAPTAHARI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. BUDIMAN Ginting2. Bastari3. Utary Maharany Barus PPJB-TB is a preliminary agreement on land and building right transfer between the seller and the buyer before the real Purchase Contract is signed. The issuance of PP No.34/2016 causes legal certainty in which PPJB-TB, PPh-Final payable, and the implementation of tax assessment on PPh in PPJB become the responsibility of a Notary. PPh-Final payable in PP No.34/2016 has met the principle of justice since it belongs to a person who has additional income from land and building right transfer or to those who transfer their land and building through PPJB and/or its addendum. Concerning settled PPJB-TB, related to its tax, the implementation of Settled PPJB-TB does not become the object of BPHTB and its exception so that there is legal uncertainty for PPJB as the object and is regulated on BPHTB in Law No.28/2009 on Regional Tax and Retribution and in the regulation on PPh in PP No.34/2016.